Discovery of a chalcone derivative as an anti-fibrotic agent targeting transforming growth factor-β1 signaling: Potential therapy of renal fibrosis - Poolsri W. (2023)
As a final common pathway of renal injuries, renal fibrosis leads to chronic kidney disease (CKD). Currently, there is no safe and effective therapy to prevent the progression of renal fibrosis to CKD. Inhibition of transforming growth factor-β1 (TGF-β1) pathway is proposed as one of the most promising approaches for anti-renal fibrosis therapies. This study aimed to identify novel anti-fibrotic agents using the TGF-β1-induced fibrosis in renal proximal tubule epithelial cells (RPTEC) and characterize their mechanism of action as well as in vivo efficacy. By screening 362 natural product-based compounds for their ability to reduce collagen accumulation assessed by picro-sirius red (PSR) staining in RPTEC cells, a chalcone derivative AD-021 was identified as an anti-fibrotic agent with IC50 of 14.93 μM. AD-021 suppressed TGF-β1-induced collagen production, expression of pro-fibrotic proteins (fibronectin and α-smooth muscle actin (αSMA)), and Smad-dependent and Smad-independent signaling pathways via suppression of TGF-β receptor II (TGFβRII) phosphorylation in RPTEC cells. Furthermore, TGF-β1-induced mitochondrial fission in RPTEC cells was ameliorated by AD-021 via mechanisms involving inhibition of Drp1 phosphorylation. In a mouse model of unilateral ureteral obstruction (UUO)-induced renal fibrosis, AD-021 reduced plasma TGF-β1, ameliorated renal fibrosis and improved renal function. Collectively, AD-021 represents a novel class of natural product-based anti-fibrotic agent that has therapeutic potential in the prevention of fibrosis-associated renal disorders including CKD.